(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In 2023, in-kind and experimental measurement-researches were carried out in order to study the efficiency of water resources, the processes and morphology of the channel bed of the Great Fergana Main Canal. In particular, in the section of the Big Fergana main channel from PK1949+00 to 2042+00, in 22 tributaries, along the cross section of the channel, studies were conducted to study the water consumption, speed, depth and bed morphology of each tributary using the SONTEK S5 acoustic doppler profilograph with GPS device. .